Femtosecond laser modified Fabry-Pérot interferometer optical fibre tip sensor for monitoring dissolved oxygen - Ioannou, Andreas; Zarvou, Sotia; Christofi, Aristi; Kalli, Kyriacos (My University, 2022)
We present the design of an optical fibre tip sensor for monitoring dissolved oxygen. It is based on the creation and modification of an all-fibre Fabry-Pérot interferometer, produced in a three-step process. First, fibre cavities are created in two fibres using a femtosecond laser that are then joined using arc fusion splicing, thereby forming a miniature fibre Fabry-Pérot interferometer. Finally, the femtosecond laser is used to create two symmetrical micro-holes exactly at the location of the Fabry-Pérot cavity and on opposite sides of the fibre, allowing liquids to access the cavity and perform refractive index sensing. For the dissolved oxygen sensing, the fibre sensor was first immersed in a hemoglobin solution to deposit a thin layer at the walls of the cavity to give oxygen discrimination. The sensitivity to the ratio of dissolved carbon dioxide to dissolved oxygen was demonstrated via the conversion of carboxyhemoglobin to oxyhemoglobin inside the cavity, thus changing the refractive index of the hemoglobin. The complete sensor was tested in two solutions with different oxygen concentrations and having the same refractive index and temperature. The first sample was a PBS solution dissolved in deionized water, which absorbs CO2 from the air after it is produced. The second sample was a PBS solution with sodium bicarbonate to ensure that all solution-state hemoglobin was converted to oxyhemoglobin, by converting the dissolved carbon dioxide into carbonate groups. We observed the difference between the two solutions that have the same refractive index and different oxygen levels by the means of a wavelength shift and amplitude change in the Fabry-Pérot interferometer spectrum due to the oxygenation of the hemoglobin.
Keywords: femtosecond laser; miniature fibre interferometer; Optical fibre sensors; oxygen sensor